Evaluation of Dietary Aspergillus Meal on Intestinal Morphometry in Turkey Poults - Tellez , G.; Nava, G.M.; Vicente, J.L.; Franceschi, M. De; Morales, E.J.; Prado, O.; Terraes, J.C.; Hargis, B.M. (International Journal of Poultry Science, 2010)
A trial was conducted to evaluate the influence of dietary Aspergillus Meal (AM) prebiotic on intestinal development, morphology in turkey poults. Day-old Nicholas poults (n = 100) were randomly assigned to two groups. Poults in each group were divided and placed in floor pens with 50 poults each. One group served as a control and received a ration containing no added AM prebiotic. Poults in the treatment group were provided a ration supplemented with 0.2% AM prebiotic. Each dietary regimen and water were provided ad libitum to 30 days of age. Poults were humanely killed by CO2 inhalation and specimens of duodenum and distal ileum were collected at 10, 20 and 30 days. Histology sections were cut (5 μm) and stained with haematoxylin and eosin and combinations of either of periodic acid-Schiff with alcian blue, or high iron diamine with alcian blue stains to evaluate 20 intact villi on each section. The morphometric variables analyzed included villi height, villi surface area and crypt depth. In addition, goblet cells, classified as neutral, acidic or sulpho mucin cells, respectively, were quantitative for each treatment group. At all times of evaluation, AM prebiotic significantly increased the number of acid mucin cells in the duodenum, neutral mucin cells in the ileum and sulpho mucin cells in the duodenum and ileum. Villi height and villi surface area of both duodenum and ileum were significantly increased at days 10 and 30 compared to control. The present study suggest that AM prebiotic has an impact on the mucosal architecture and goblet cells proliferation in the duodenum and ileum of neonate poults.